Loss of Pleiotropic Regulatory Functions in Tannin1, the Sorghum Ortholog of Arabidopsis Master Regulator TTG1 - Anthony Schuh; Geoffrey P. Morris (Plant Direct)
ABSTRACT Transcriptional master regulators are often targeted to improve plant traits, but antagonistic pleiotropic effects of these regulators can hamper this approach. The Myb‐bHLH‐WDR (MBW) complex is a broadly conserved transcriptional regulator affecting pigmentation, biotic stress resistance, and abiotic stress tolerance. We investigated the function of sorghum grain pigmentation regulator Tannin1, the ortholog of Arabidopsis pleiotropic WD40 regulator TTG1, to test for conserved pleiotropic regulatory effects and to better understand the evolution of the MBW complex in Poaceae. We characterized genome‐wide differential expression of leaf tissue using RNA sequencing in near‐isogenic lines (NILs) that contrasted wildtype Tan1 and loss‐of‐function tan1‐b alleles, under optimal temperature and chilling stress. Notably, Gene Ontology analyses revealed no pathways with differential expression between Tan1 and tan1‐b NILs, suggesting that, in contrast to Arabidopsis TTG1, Tannin1 has no pleiotropic regulatory role in leaves. Further, NILs had no visible difference in anthocyanin pigmentation, and no genes with known or expected function in flavonoid synthesis were differentially expressed. Genome‐wide, only 18 total genes were differentially expressed between NILs, with six of these genes located inside the NIL introgression region, an observation most parsimoniously explained by cis‐regulatory effects unrelated to Tannin1 regulation. Comparing our findings with known function of TTG1 orthologs in maize, rice, and Arabidopsis, we conclude that pleiotropic regulatory function in leaf tissue was likely lost in panicoid grass evolution before the sorghum‐maize split. These findings inform future molecular breeding of MBW regulated traits and highlight the benefit of subfunctionalization to relieve pleiotropic constraints.